Terapia ipostimolante mediante blocchi anestetici nel dolore cranio-facciale - Hypostimulation therapy using anesthetic blocks in the craniofacial pain - Claudio Antonio Caputi; Vincenzo Firetto (Publiediting, 2012)
The therapeutic value of greater occipital and supraorbital nerve blokade in 262 patients with migraine, unresponsive to several combinations of pharmacological treatments, was investigated. Two-hundred-fourteen patients (82%) responded well and maintained a favorable response during the six-month period of observation. Furthermore, the same treatment has been administered to 180 patients who suffered from trigeminal neuralgia. 103 of them received a complete remission of painful attacks while 45 persons had a partial remission of the same symptoms according to a six and twelve month follow-up survey. The trigeminal nerve hypersensitization coud be interrupted by the performed procedure as the following facial trigger point suppression would suggest us. We hope that this clinical experience, together with a correct neurophysiological study, could prove be useful in clarify pathogenetic aspects.